Pembelajaran Matematika Melalui Koding - Ani Ismayani (Idealmathedu: Indonesian Digital Journal of Mathematics and Education, 2022)
Coding or computer programming is believed to promote students' computational thinking skills, one of the essential skills in the 21st century. Nowadays, computational thinking is even considered as a new type of literacy that students need to master. By means of coding, students are trained to be competent in problem solving through various activities that stimulate logical, creative, critical, and analytical thinking. These qualities make coding widely promoted as medium and means of learning mathematics. This paper discusses how coding can be integrated in mathematics learning to achieve its goals, grounded on some references tracing and empirical observations in a limited scope. Furthermore, several examples of coding activities and their forms of integration with mathematics lessons at school are discussed.